LEGAL ANALYSIS OF ISLAMIC COMMERCIAL LAW ON THE PRACTICE OF EXPLOITING MARINE RESOURCES IN COASTAL AREAS (A STUDY OF MUAMALAH JURISPRUDENCE AND ECOLOGICAL ETHICS) - Fahman Urdawi Nasution; Muhammad Natsir; Hendri Dwitanto (NOMOI Law Review, 2026)
This research analyzes the practices of marine resource exploitation in the coastal area of East Aceh from the perspective of Islamic commercial law, focusing on a review of fiqh muamalah and ecological ethics. East Aceh, as a coastal area with significant marine potential, faces various problems of excessive exploitation such as the use of trawl nets, overfishing, and degradation of mangrove ecosystems. This study aims to assess the conformity of marine resource management practices with the principles of Islamic law, analyze the impact of excessive exploitation on maqashid sharia, and formulate a sustainable management framework based on Islamic values. The research method used is qualitative with a library research approach, analyzing Islamic legal literature, scientific journals, and related policy documents. The research findings indicate that the practice of exploiting marine resources in East Aceh contradicts the principles of fiqh muamalah such as la darar wa la dirar (not causing harm), the prohibition of israf (wastefulness), and the concept of amanah in resource management. From the perspective of Islamic ecological ethics, these practices violate the principle of mizan (balance), hifz al-bi'ah (environmental preservation) as part of maqashid sharia, as well as the responsibility of khalifah fi al-ardh. The conclusion of the research emphasizes the need for a transformation in the management of marine resources that integrates the principles of Islamic law with sustainable practices, through the application of a sharia economic system, the development of a halal value chain, and strengthening the role of Islamic institutions in education and supervision.